2019
DOI: 10.3390/coatings9060396
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Corrosion Resistance and Cytocompatibility of a Bioactive Micro-Arc Oxidation Coating on AZ31 Mg Alloy

Abstract: Magnesium alloys have recently been attracting attention as a degradable biomaterial. They have advantages including non-toxicity, biocompatibility, and biodegradability. To develop magnesium alloys into biodegradable medical materials, previous research has quantitatively analyzed magnesium alloy corrosion by focusing on the overall changes in the alloy. Therefore, the objective of this study is to develop a bioactive material by applying a ceramic oxide coating (magnesia) on AZ31 magnesium alloy through micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…The SEM morphology of the Ca-P containing MAO samples with typical pancake-like structure (a cratered structure with a central pore), as shown in Figure 2 . Compare with our previous study [ 30 ], the Ca-P containing MAO samples showed a relatively uniform and smooth surface than the Ca-P-free MAO samples. Calcium phosphate had very low solubility in water [ 33 ] because the individual calcium cations and phosphate anions were tightly bonded to each other in an aqueous medium.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…The SEM morphology of the Ca-P containing MAO samples with typical pancake-like structure (a cratered structure with a central pore), as shown in Figure 2 . Compare with our previous study [ 30 ], the Ca-P containing MAO samples showed a relatively uniform and smooth surface than the Ca-P-free MAO samples. Calcium phosphate had very low solubility in water [ 33 ] because the individual calcium cations and phosphate anions were tightly bonded to each other in an aqueous medium.…”
Section: Resultscontrasting
confidence: 54%
“…The plates were then ultrasonically cleaned in acetone, rinsed with deionized water and dried in a hot air stream of 60 °C. The process to prepare MAO coatings on the AZ31 magnesium surface was carried out on a pulse power generator (MIRDC) with work voltage up to 400 V, current up to 10 A, duty cycle at 20% and the electrical frequency at 4000 Hz for 30 min [ 30 ]. The water bath made of stainless steel has 45 L water capacity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium alloys are widely used in many fields because of their light weight, good damping capacity, and recycling potential [1][2][3]. Unfortunately, the corrosion resistance of magnesium alloys in many engineering applications is insufficient [4,5] and methods such as micro-arc oxidation [6,7], laser cladding [8,9], plasma electrolytic oxidation [10,11] and ion implantation [12][13][14][15] have been proposed to improve the corrosion properties. For example, Zn [16,17], Zr [18], Nd [19], C 2 H 2 [20] and Si [21] ion implantations have been conducted on Mg alloys to improve the surface properties [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the corrosion resistance of magnesium alloys is not good enough [6,7]. To date, many methods have been carried out to improve the corrosion properties of magnesium alloys such as microarc oxidation [8,9], laser cladding [10,11], and ion implantation [12][13][14][15][16]. Ion implantation causes the substrate and coating have a good binding force compared to other methods.…”
Section: Introductionmentioning
confidence: 99%